2020
DOI: 10.2147/cmar.s253345
|View full text |Cite
|
Sign up to set email alerts
|

<p>Regulation of Autophagy by Non-Steroidal Anti-Inflammatory Drugs in Cancer</p>

Abstract: Cancer is the leading cause of death, placing a substantial global health burden. The development of the most effective treatment regimen is the unmet clinical need for cancer. Inflammation plays a role in tumorigenesis and progression, and anti-inflammation may be a promising option for cancer management and prevention. Emerging studies have shown that non-steroidal anti-inflammatory drugs (NSAIDs) display anticarcinogenic and chemopreventive properties through the regulation of autophagy in certain types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 97 publications
0
17
0
1
Order By: Relevance
“…Consistently, DMC also induces apoptosis in NPC cells, proved by an increase of the cleavage of caspase-3 and PARP as well as a decrease in Bcl-2/Bax level after DMC exposure. In addition, a considerable amount of literature has demonstrated that anti-cancer drugs caused cells death is found to be associated with autophagy [ 24 , 25 ]. Of note, recent studies demonstrated celecoxib is determined to be autophagy inducer or inhibitor linked with preventing the occurrence and development of carcinoma [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, DMC also induces apoptosis in NPC cells, proved by an increase of the cleavage of caspase-3 and PARP as well as a decrease in Bcl-2/Bax level after DMC exposure. In addition, a considerable amount of literature has demonstrated that anti-cancer drugs caused cells death is found to be associated with autophagy [ 24 , 25 ]. Of note, recent studies demonstrated celecoxib is determined to be autophagy inducer or inhibitor linked with preventing the occurrence and development of carcinoma [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selective COX-2 inhibitors, like rofecoxib and celecoxib, have improved safety profiles for gastric side effects. In addition, they depress prostacyclin, an atheroprotective agent, but not COX-1-related thromboxane, a proaggregatory agent and vasoconstrictor, which might predispose patients to heart attack and stroke [ 52 ].…”
Section: Current Nsaid Pharmacological Approaches For Dental Pain Treatmentmentioning
confidence: 99%
“…Moreover, NSAIDs have been shown to inhibit Bcl-2 and mTOR kinase through the inhibition of the HGF/MET autocrine loop, causing induction of autophagy and a decrease in drug resistance. 38 Interestingly, a recent retrospective study supported that in head and neck cancer the subpopulation of patients that would benefit from NSAID use is restricted to those whose tumors exhibit catalytic subunit of phosphatidylinositol 3-kinase (PIK3CA) genomic alterations. Cancerassociated mutations in PIK3CA promote signaling via the PI3K pathway, and activation of the PI3K pathway leads to induction of COX-2 enzyme and production of immunosuppressive prostaglandin E2 (PGE2).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NSAIDs induce the expression of tumor suppressor protein NSAID-activated gene-1 (NAG-1), which has been shown to exhibit proapoptotic and antitumorigenic activities. , NSAIDs can also exert their anticancer and chemopreventive activities through the regulation of autophagy via the interference with the expression of Beclin-1, a well-established regulator of the autophagic pathway, the Bcl-2 family of proteins, and the PI3K/AKT, AMPK, and MAP kinases. Moreover, NSAIDs have been shown to inhibit Bcl-2 and mTOR kinase through the inhibition of the HGF/MET autocrine loop, causing induction of autophagy and a decrease in drug resistance . Interestingly, a recent retrospective study supported that in head and neck cancer the subpopulation of patients that would benefit from NSAID use is restricted to those whose tumors exhibit catalytic subunit of phosphatidylinositol 3-kinase (PIK3CA) genomic alterations.…”
Section: Introductionmentioning
confidence: 99%